Using nomophobia severity to predict illegal smartphone use while driving - F. Kaviani; K.L. Young; S. Koppel (Computers in Human Behavior Reports, 2022)
The fear of being without a mobile phone has emerged as a global psycho-social phenomenon impacting smartphone users and their behaviour. Determining whether higher levels of nomophobia are associated with an increased likelihood of illegal smartphone use in vehicles may provide driver licencing authorities with avenues to reduce risk by developing programs and training aimed at mitigating nomophobia. This study builds upon a previous analysis that revealed only one of nomophobia's four factors—the fear of being without access to information—predicted the likelihood of illegal smartphone use while driving. By measuring total nomophobia scores in terms of severity, not factors, this study identified a stronger relationship than previously thought between driver's illegal smartphone use and the fear of being without a mobile phone. Indeed, using a sample of 2773 Australian smartphone users from the state of Victoria, individuals with ‘severe’ nomophobia were 85% more likely to engage in illegal use while driving. In other words, the odds of engaging in illegal smartphone use among those with severe nomophobia increased by a factor of 6.6. Given the global prevalence of severe nomophobia is over 20%, these findings become significant for road users around the world, especially in low to middle income countries where 90% of road traffic deaths occur. Developing educational and/or behavioural programs reducing nomophobia may reduce road traffic deaths.